2016
DOI: 10.1210/jc.2015-1710
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Primary Adrenal Insufficiency: An Endocrine Society Clinical Practice Guideline

Abstract: We recommend diagnostic tests for the exclusion of primary adrenal insufficiency in all patients with indicative clinical symptoms or signs. In particular, we suggest a low diagnostic (and therapeutic) threshold in acutely ill patients, as well as in patients with predisposing factors. This is also recommended for pregnant women with unexplained persistent nausea, fatigue, and hypotension. We recommend a short corticotropin test (250 μg) as the "gold standard" diagnostic tool to establish the diagnosis. If a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
1,350
3
110

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,284 publications
(1,583 citation statements)
references
References 186 publications
15
1,350
3
110
Order By: Relevance
“…We found one single-center randomized trial that compared low-dose ACTH (1 µg) stimulation test with total random cortisol for diagnosis of adrenal insufficiency in 59 adults with septic shock [10]. Compared with total random cortisol, the low-dose ACTH test was better able to predict a longer duration of vasopressor requirement and hemodynamic response to corticosteroids.…”
Section: Rationalementioning
confidence: 99%
“…We found one single-center randomized trial that compared low-dose ACTH (1 µg) stimulation test with total random cortisol for diagnosis of adrenal insufficiency in 59 adults with septic shock [10]. Compared with total random cortisol, the low-dose ACTH test was better able to predict a longer duration of vasopressor requirement and hemodynamic response to corticosteroids.…”
Section: Rationalementioning
confidence: 99%
“…Eine diagnostische Abklärung auf eine primäre Nebenniereninsuffizienz wird bei akut kranken PatientInnen empfohlen, die an anderweitig nicht erklärbaren Symptome/Beschwerden leiden, welche als suggestiv für eine primäre Nebenniereninsuffizienz angesehen werden: Volumenmangel, Hypotonie,Hyponatriämie,Hyperkaliämie,Fieber,abdominelle Schmerzen,Hyperpigmentierung, oder, speziell bei Kindern, Hypoglykämie [1]. Bei ausgeprägter Symptomatik sollte jedoch schon bei Verdacht auf eine Nebenniereninsuffizienz (Verdacht auf Addison Krise) eine entsprechende Therapie (z.…”
Section: Diagnostikunclassified
“…Unfortunately, we as treating physicians have a tendency to give supraphysiological glucocorticoid doses to minimize the risk of adrenal crisis in AD and CAH, but also to suppress adrenal androgens in the latter [4,10,11]. However, from a 2-year prospective study it was recently reported that a reduction of the glucocorticoid doses in AD and CAH led to improved BMD without increased risk of adrenal crisis while dose increments decreased BMD [12].…”
mentioning
confidence: 99%